Adverse reactions to oil-emulsified (ISA-70) Newcastle disease vaccine in a pigeon flock - Farjanikish, Ghasem; Khodakaram-Tafti, Azizollah; Aslnajjari, Amir H. (Brazilian Journal of Veterinary Pathology, 2016)
Oil adjuvants in combination with inactivated vaccines against several avian diseases are widely used. In spite of some advantages of oil adjuvants, a local tissue reaction has been reported in some animals. In this report, about 30 birds of a flock of pigeons with 40 birds, developed scattered small to large nodules about 5 mm to 2 cm in diameter in subcutaneous tissues and pectoral muscles after intramuscularly injection of an oil-emulsified (ISA-70) Newcastle disease vaccine. Histopathologic examination showed granulomatous and cystic reactions in the site of injection. Bacteriological examinations as well as fresh smears stained with Ziehl-Neelsen, Brown-Brenn Gram and PAS stains were void of bacteria or fungi. It may be prudent to consider the potential for induction of adverse reaction of vaccine formulations containing mineral oils as adjuvant in pigeons.